Objective and subjective barriers to the effective pediatric iron deficiency anemia control: results of questionnaire assessment of pediatricians and parents - Ivan V. Fisyun; Tatiana A. Kuznetsova (Union of pediatricians of Russia, 2023)
Background. Iron deficiency anemia (IDA) remains a pressing pediatric issue to date. Despite the availability of clinical guidelines and other publications that highlight the objective causes for the lack of effectiveness of treatment and prevention of IDA in children, the subjective reasons are unrenowned.Objective. The aim of the study is to evaluate health beliefs of pediatricians and parents on the problem of anemia in children to investigation into the objective and subjective causes for inadequate control of iron deficiency conditions in childhood.Materials and methods. In September 2022, single-step parallel survey of pediatricians and parents on the problem of IDA in children was conducted by random sampling technique using original questionnaires. The questions were formulated on five topics and related to a common understanding of the term "anemia"; priority reference sources; availability of diagnosis of IDA in medical institutions (MI); the position of pediatricians and parents on the treatment and prevention of IDA in children. Based on the results, the main subjective and objective barriers to the control of IDA in children are identified. The χ2 method was used for the comparative evaluation of the responses. The differences were considered significant at statistical significance of p < 0.05.Results. Pediatricians (n = 81) and parents (n = 363) from 23 members of the Russian Federation took the survey. Among the objective barriers to the IDA control in children, the low availability of serum ferritin in MI, difficulties of venous access in children, a shortage of a range of iron preparations for children on Russian market were revealed. The subjective barriers were the skepticism of pediatricians and parents about the necessity for conservative prevention of IDA; poor knowledge of the criteria for diagnosis IDA and completion of IDA therapy by pediatricians; insufficient independence and selectivity of pediatricians when prescribing iron preparations; orientation of the majority of parents (93.7%) to the opinion of doctors, along with the actual rarity of full-fledged conversations with a pediatrician (16.3%).Conclusion. The main limitation of this study was the random sample method inclusion of respondents due to the impossibility of conducting a full-fledged population study. Elimination of the revealed subjective and objective factors can contribute to improving the detection of IDA in children, early appointment and higher effectiveness of treatment, reducing the frequency of disease recurrences, as well as increasing the confidence of parents in pediatricians.